Juzgado General de Indios del Perú o Juzgado Particular de Indios de el cercado de Lima - Borah, Woodrow (Revista Chilena de Historia del Derecho, 1970)
For students of colonial institutions in the Viceroyalty of New Spain, and in particular the Audiencia of Mexico, reports of the existence in Peru of a Juzgado General de Zndios del Perú paralleling the Juzgaclo General & Indios de la Nueva España in nature and function have presented something of a puzle.